Versatile Roles of K63-Linked Ubiquitin Chains in Trafficking - Erpapazoglou, Zoi (Cells, 2014)
Modification by Lys63-linked ubiquitin (UbK63) chains is the second most abundant form of ubiquitylation. In addition to their role in DNA repair or kinase activation, UbK63 chains interfere with multiple steps of intracellular trafficking. UbK63 chains decorate many plasma membrane proteins, providing a signal that is often, but not always, required for their internalization. In yeast, plants, worms and mammals, this same modification appears to be critical for efficient sorting to multivesicular bodies and subsequent lysosomal degradation. UbK63 chains are also one of the modifications involved in various forms of autophagy (mitophagy, xenophagy, or aggrephagy). Here, in the context of trafficking, we report recent structural studies investigating UbK63 chains assembly by various E2/E3 pairs, disassembly by deubiquitylases, and specifically recognition as sorting signals by receptors carrying Ub-binding domains, often acting in tandem. In addition, we address emerging and unanticipated roles of UbK63 chains in various recycling pathways that function by activating nucleators required for actin polymerization, as well as in the transient recruitment of signaling molecules at the plasma or ER membrane. In this review, we describe recent advances that converge to elucidate the mechanisms underlying the wealth of trafficking functions of UbK63 chains.